Towards gender-responsive banana research for development in the East-African Highlands - Rietveld, Anne M.; Farnworth, Cathy Rozel (2018)
Banana production is an important livelihood for farming households in the East-African highlands as food and as a source of income. Banana is a crop with a long history in this region. Although not originating from Africa, it is believed bananas have been cultivated in this region since 2000 BC. It is not surprising that the technical aspects of banana production are intertwined with rituals, habits, and social norms. In this guide, we highlight and discuss social norms surrounding banana production, zooming in specifically on gender norms. Understanding these norms coupled with the ability to address them is essential for the development and design of high-quality banana-focused research for development (R4D) projects which benefit men as well as women.